1998
DOI: 10.1210/endo.139.9.6202
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY, Glucagon-Like Peptide-1, and Neurotensin Responses to Luminal Factors in the Isolated Vascularly Perfused Rat Ileum

Abstract: Exposure of the ileum to nutrients markedly inhibits several upper gastrointestinal functions. Hormonal peptides of the ileal wall, i.e. peptide YY (PYY), glucagon-like peptide-1 (GLP-1), and neurotensin (NT), are thought to play a role in this negative feedback mechanism. The present study was conducted to comparatively assess the secretion of PYY, GLP-1, and NT upon luminal infusion of a variety of individual luminal factors in the isolated vascularly perfused rat ileum preparation. PYY, GLP-1, and NT were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 31 publications
3
59
2
Order By: Relevance
“…Cani et al (2009) have recently shown that microbial fermentation of prebiotics is associated with an increase in GLP-1 and PYY production in healthy adults. In rodents, the by-products of microbial fermentation of dietary fiber, short chain fatty acids have been shown to directly stimulate PYY secretion (Dumoulin et al, 1998). Konjac glucomannan, one of the primary fiber components of PGX, has been shown to increase fecal concentrations of acetate, propionate and butyrate in humans (Chen et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Cani et al (2009) have recently shown that microbial fermentation of prebiotics is associated with an increase in GLP-1 and PYY production in healthy adults. In rodents, the by-products of microbial fermentation of dietary fiber, short chain fatty acids have been shown to directly stimulate PYY secretion (Dumoulin et al, 1998). Konjac glucomannan, one of the primary fiber components of PGX, has been shown to increase fecal concentrations of acetate, propionate and butyrate in humans (Chen et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The finding that G␣ gust and T1Rs are expressed in enteroendocrine cells, whereas SGLT1 is expressed in enterocytes, implies that a chemical signaling event takes place between the chemosensory enteroendocrine cells and absorptive enterocytes. Enteroendocrine cells, in response to luminal nutrients, secrete endocrine hormones including cholecystokinin (CCK), peptide tyrosine tyrosine (PYY), neurotensin, GLP-1, GLP-2, and GIP (18,19,(22)(23)(24). GLP-1 and GIP, known as incretins, are secreted in response to dietary sugars, and influence glucose transport, metabolism, and homeostasis (25).…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 and GIP, known as incretins, are secreted in response to dietary sugars, and influence glucose transport, metabolism, and homeostasis (25). Infusion of the intestinal lumen with glucose, galactose, fructose, 3-O-methyl-D-glucose and ␣-methyl-D-glucose causes GIP and GLP-1 secretion in rats, pigs, and humans (22)(23)(24). These sugars also increase SGLT1 expression when infused into the intestinal lumen (4,6,26).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly they are both secreted from the same enteroendocrine cells, the Lcells. Because only high concentrations of glucose and fatty acids directly infused into the vascularly perfused rat ileum where effective in stimulating PYY secretion, it is thought that this mechanism represents the so called ileal brake, that operates only in cases of malabsorption or maldigestion (Dumoulin et al, 1998). However, since hydrolyzed protein was even more potent in stimulating PYY release from the perfused rat ileum (Dumoulin et al, 1998), and compared to high fat and high carbohydrate diets, high protein diet produced the highest PYY plasma levels (Batterham et al, 2006), it is possible that digested protein levels in the distal small intestine are high enough to physiologically stimulate PYY release.…”
Section: Lower Gut: the Ileal Brake Hormones Glp-1 And Pyymentioning
confidence: 99%